THE ECONOMIC FEASIBILITY OF HONEY PRODUCTION IN A BEE-KEEPING PROJECT- ABU GHRAIB-BAGHDAD PROVINCE AS A CASE STUDY -FOR THE PRODUCTION SEASON 2011- - Jasim . M . Hbeeb; Ahmed . M . Faris; Zuhal R. ALhuseny (Mesopotamia Journal of Agriculture)
ABSTRACT The research aims at calculating the economic feasibility of honey production by choosing a random sample of beekeeping project in Abu- Ghraib. The questionnaire data concern the production season 2011. The results showed that all criteria for the calculation of economic feasibility, which were applied on research sample, were profitable. The results also showed that fixed costs consisted about 84% while the variable costs consisted 16% of total costs. The results of the revenues for bee-keeping project in the sample showed that the net profit was ID (9692000), This was due to the large revenues in comparison with low costs which is consistent with economic logic. The revenue of each invested dinar was (4.33) dinars which expresses the good economic feasibility. The project management recovered the invested capital in three months period when the pay-back period criteria was applied which indicates the very short period in comparison with the pay-back period of other projects .